Peer and self-evaluation using active teaching method (Research, Society and Development, 2020)
Nowadays, new methodologies have been used to complementing and assisting in the fixation of knowledge. So, the aim of this work was apply a active education methods using a study case methodology to assess the critical competence in objective and subjective assessments and self-assessment, and to analyze the results obtained in a qualitative way. Students developed content, presented seminars, evaluate their peers objectively (assigning grades) and subjective (selecting according to preference) and also performed the self-assessment. Based on the grades attributed by the students, the ability to evaluate by peers by comparing variances was evaluated. From the results obtained, we can conclude that there is a mutual influence on the two types of evaluations used in this research. Students were able to evaluate their peers and also self-evaluation. There is consistency between different evaluators and also when compared to self-criticism. From the research on the experience of active teaching, it is possible to observe the growing preference of students for this teaching methodology.